Research Trends of Gamification in EFL/ESL Classrooms Between 2017 and 2024: A Bibliometric Analysis - Nurul Amalina; Ella Wulandari; Dyah Setyowati Ciptaningrum (Journal of English Language Studies, 2026)
This study maps global research trends on gamification in EFL and ESL classrooms from 2017 to 2024. Using Scopus metadata and following PRISMA procedures, this study compiled a dataset that reduced an initial 300 records to 191 eligible journal articles. Bibliometric analyses were conducted through VOSviewer and Biblioshiny to examine annual publication patterns, productive authors and countries, co-occurrence networks, and dominant keywords. The results show a steady rise in publications, with a remarkable increase from 2023 to 2024. China, Indonesia, and Malaysia emerge as the most productive countries, while Melor Md Yunus stands out as the most productive author. Keyword mapping highlights gamification, game-based learning, motivation, vocabulary learning, Kahoot, and Quizizz as central themes, with clusters indicating links to mobile learning, augmented reality, and various affective variables. The analysis also points to several gaps, such as the concentration of studies on specific tools and the limited exploration of other instructional contexts. Based on these findings, this study suggests that future research should expand the scope of learning environments and investigate a wider range of pedagogical designs to better understand how gamification can support different dimensions of language learning. The overall results provide a systematic overview that can guide researchers and educators in developing more informed approaches to integrating gamified strategies in language teaching.